'Keep fit' exercise interventions to improve health, fitness and well‐being of children and young people who use wheelchairs: mixed‐method systematic review protocol. (18th May 2014) - O'Brien, Thomas D.; Noyes, Jane; Spencer, Llinos Haf; Kubis, Hans‐Peter; Hastings, Richard P.; Edwards, Rhiannon T.; Bray, Nathan; Whitaker, Rhiannon
Abstract Aim This mixed‐method systematic review aims to establish the current evidence base for 'keep fit', exercise or physical activity interventions for children and young people who use wheelchairs. Background Nurses have a vital health promotion, motivational and monitoring role in optimizing the health and well‐being of disabled children. Children with mobility impairments are prone to have low participation levels in physical activity, which reduces fitness and well‐being. Effective physical activity interventions that are fun and engaging for children are required to promote habitual participation as part of a healthy lifestyle. Previous intervention programmes have been trialled, but little is known about the most effective types of exercise to improve the fitness of young wheelchair users. Design Mixed‐method design using Cochrane systematic processes. Evidence regarding physiological and psychological effectiveness, health economics, user perspectives and service evaluations will be included and analysed under distinct streams. Methods The project was funded from October 2012. Multiple databases will be searched using search strings combining relevant medical subheadings and intervention‐specific terms. Articles will also be identified from ancestral references and by approaching authors to identify unpublished work. Only studies or reports evaluating the effectiveness, participation experiences or cost of a physical activity programme will be included. Separate analyses will be performed for each data stream, including a meta‐analysis if sufficient homogeneity exists and thematic analyses. Findings across streams will be synthesized in an overarching narrative summary. Discussion Evidence from the first systematic review of this type will inform development of effective child‐centred physical activity interventions and their evaluation.